Resolving the Gender Empowerment Equation in agricultural research: A systems approach - Tegbaru, A.; FitzSimons, J.; Kirscht, H.; Hillbur, P. (2015)
The aim of this paper was to bridge the socio-technical divide in agricultural systems research by providing an approach that addresses marginalized groups, particularly rural women, and their access to and ownership of agricultural intensification processes. By revisiting social systems theory and the evolution of gender approaches in the CGIAR, the paper provides socio-spatial perspectives on gender supported by a landscape approach to innovation, agency and empowerment. A systems approach to empowerment is critical to make agricultural research-for-development gender transformative. The paper explores a more inclusive CGIAR systems research in the light of the ambitions to alleviate poverty, improve nutrition and income without compromising the long-term productivity of the natural environment. The empowering dimension of systems research is distinct from that of commodity focused value chain approaches and other traditional gender approaches within agriculture which have separated gender and development from systems thinking.